Fibroblast growth factor receptor signaling in estrogen receptor-positive breast cancer: mechanisms and role in endocrine resistance - Marin, Arnaldo; Morales, Fernanda; Walbaum, Benjamín (Frontiers in Oncology, 2024)
Fibroblast Growth Factor Receptors (FGFRs) play a significant role in Estrogen Receptor-positive (ER+) breast cancer by contributing to tumorigenesis and endocrine resistance. This review explores the structure, signaling pathways, and implications of FGFRs, particularly FGFR1, FGFR2, FGFR3, and FGFR4, in ER+ breast cancer. FGFR1 is frequently amplified, especially in aggressive Luminal B-like tumors, and its amplification is associated with poor prognosis and treatment resistance. The co-amplification of FGFR1 with oncogenes like EIF4EBP1 and NSD3 complicates its role as a standalone oncogenic driver. FGFR2 amplification, though less common, is critical in hormone receptor regulation, driving proliferation and treatment resistance. FGFR3 and FGFR4 also contribute to endocrine resistance through various mechanisms, including the activation of alternate signaling pathways like PI3K/AKT/mTOR and RAS/RAF/MEK/ERK. Endocrine resistance remains a major clinical challenge, with around 70% of breast cancers initially hormone receptor positive. Despite the success of CDK 4/6 inhibitors in combination with endocrine therapy (ET), resistance often develops, necessitating new treatment strategies. FGFR inhibitors have shown potential in preclinical studies, but clinical trials have yielded limited success due to off-target toxicities and lack of predictive biomarkers. Current clinical trials, including those evaluating FGFR inhibitors like erdafitinib, lucitanib, and dovitinib, have demonstrated mixed outcomes, underscoring the complexity of FGFR signaling in breast cancer. The interplay between FGFR and other signaling pathways highlights the need for comprehensive molecular profiling and personalized treatment approaches. Future research should focus on identifying robust biomarkers and developing combination therapies to enhance the efficacy of FGFR-targeted treatments. In conclusion, targeting FGFR signaling in ER+ breast cancer presents both challenges and opportunities. A deeper understanding of the molecular mechanisms and resistance pathways is crucial for the successful integration of FGFR inhibitors into clinical practice, aiming to improve outcomes for patients with endocrine-resistant breast cancer.